2021
DOI: 10.1007/s11469-021-00577-0
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of COVID-19 Traumatic Stressors on Mental Health: Is COVID-19 a New Trauma Type

Abstract: COVID-19 is a new type of trauma that has never been conceptually or empirically analyzed in our discipline. This study aimed to investigate the impact of COVID-19 as traumatic stress on mental health after controlling for individuals’ previous stressors and traumas. We utilized a sample of (N = 1374) adults from seven Arab countries. We used an anonymous online questionnaire that included measures for COVID-19 traumatic stress, posttraumatic stress disorder, anxiety, depression, and cumulative stressors and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
61
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(82 citation statements)
references
References 92 publications
5
61
1
2
Order By: Relevance
“…Trauma was induced by the lockdowns introduced in successive countries, periods of withdrawal from or reinstating restrictions, the uncertainty related to the introduced vaccines and post-vaccination symptoms, and currently the uncertainty about the future in connection to the spreading infections with Delta and Omicron variants [ 14 ]. Research findings from 2019–2020 reported an increased sense of threat to life, and to motor and cognitive abilities, both in patients and in entire communities [ 15 , 16 ], increased incidence of complicated grief in connection to the death of the loved ones and the inability to be present in the last moments of their life [ 17 ] as well as loss of rituals (weddings and religious ceremonies), loss of work and financial status, loss of social support and sense of security, and even loss of one’s sense of identity [ 7 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Trauma was induced by the lockdowns introduced in successive countries, periods of withdrawal from or reinstating restrictions, the uncertainty related to the introduced vaccines and post-vaccination symptoms, and currently the uncertainty about the future in connection to the spreading infections with Delta and Omicron variants [ 14 ]. Research findings from 2019–2020 reported an increased sense of threat to life, and to motor and cognitive abilities, both in patients and in entire communities [ 15 , 16 ], increased incidence of complicated grief in connection to the death of the loved ones and the inability to be present in the last moments of their life [ 17 ] as well as loss of rituals (weddings and religious ceremonies), loss of work and financial status, loss of social support and sense of security, and even loss of one’s sense of identity [ 7 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…The COVID-19 pandemic caused the occurrence of a large number of chronic stressors such as persistent fear of contagion, fear of economic or work difficulties, (mis) information overload, uncertainty and social isolation (Kira et al, 2021). The increased levels of stress associated with the pandemic can cause depression and anxiety due to impaired psychological control and deprived hope (Gallagher et al, 2021;Sher, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Research has demonstrated that both animals and humans tend to eat comfortably nutrient-dense food in response to stress [ 92 ]. As such, it makes conceptual sense that coronavirus stress —a sudden stressor [ 93 , 94 ]—may lead to overeating. This coping activity act to reduce the psychological burden imposed by emotional distress, release cognitive resources to adjust and deal with everyday activities, which have not stopped during the COVID-19 pandemic [ 95 – 97 ].…”
Section: Introductionmentioning
confidence: 99%